Meningkatkan Keterampilan Membaca Permulaan Dan Kerjasama Siswa pada Muatan Bahasa Indonesia Menggunakan Model MAPLE di Kelas II SDN Pari-Pari - Devi Maulida Rahmah; Akhmad Riandy Agusta; Fathul Jannah; Ari Hidayat (Jurnal Pendidikan Sosial Dan Konseling, 2025)
This study addresses the low levels of student engagement, early reading proficiency, and collaboration observed during Indonesian language learning. These issues are primarily attributed to teacher-centered instructional approaches that insufficiently consider students' individual learning needs. Such approaches can impede students' ability to develop essential literacy and social skills. To overcome these challenges, the MAPLE learning model was implemented. The research aims to explore students’ engagement, early reading development, cooperative behavior, academic performance, and the overall enhancement of instructional quality through improved teacher practices. A Classroom Action Research (CAR) design was employed, conducted over four instructional cycles in the second-grade classroom at SDN Pari-pari. The participants consisted of 13 students (8 female and 5 male) in the second semester of the 2023–2024 academic year. Qualitative data were gathered through classroom observations, while student achievement was assessed using individual and group-based written tasks. The data were presented through tables, percentages, and graphical representations, and analyzed using descriptive techniques. The findings demonstrated a marked improvement in teacher activity scores, rising from 19 to 30 across four meetings. Student engagement increased from 23% to 100%, early reading proficiency improved from 23% to 85%, and collaborative skills rose from 15% to 92%. Furthermore, the percentage of students achieving mastery in learning outcomes increased from 38% to 85%. These results suggest that the MAPLE model is effective in enhancing teacher performance, student engagement, early literacy, collaboration, and academic achievement. This study may serve as a reference for educators, school leaders, and researchers seeking to improve early reading instruction and cooperative learning in primary education.